Megakaryocytes, erythropoietic and granulopoietic cells express CAL2 antibody in myeloproliferative neoplasms carrying CALR gene mutations. Issue 1 (14th September 2020) - Ali, Hebah; Puccio, Ignazio; Akarca, Ayse U.; Bob, Roshanak; Pomplun, Sabine; Keong Wong, Wai; Gupta, Rajeev; Sekhar, Mallika; Lambert, Jonathan; Al‐Masri, Hytham; Stein, Harald; Marafioti, Teresa
Abstract: Testing for the CALR mutation is included in the updated WHO criteria for essential thrombocythaemia (ET) and primary myelofibrosis (PMF). We report on the application of the CAL2 monoclonal antibody, raised against the mutated CALR gene to myeloid cases. The immunostain was used on 116 acute myeloid leukaemias (AML) and 66 myeloproliferative neoplasms (MPN) or myelodysplastic syndromes/myeloproliferative neoplasms (MDS/MPN). None of AML cases was stained by the CAL2 antibody, while 20/66 MPNs and MDS/MPNs appeared positive. Fourteen of the latter cases were studied by molecular techniques, and all showed aberrations of the CALR gene. In addition, CAL2 positivity was found in some small‐sized elements besides megakaryocytes. By double staining, these elements corresponded to small megakaryocytes as well as both erythroid and myeloid precursors. This finding suggests possible occurrence of CALR gene abnormalities in a stem cell.